2022
DOI: 10.1002/ejoc.202200818
|View full text |Cite
|
Sign up to set email alerts
|

Steric Push towards the [n+3] Hydrated Imidazoline Ring Expansion (HIRE) of Dibenzo[1.4]oxazepines and Thiazepines

Abstract: The influence of introducing substituents of increasing bulk in α position of tetracyclic imidazoline-fused heteroazepinones on the course of hydrated imidazoline ring expansion (HIRE) reaction was established. Under certain conditions, substituted β-aminoethanols can be used to obtain solely the ring expanded products from dibenzo[b,f][1,4]ox(thi)azepin-11(10H)ones while with their unsubstituted counterparts, side chain expulsion was the only observable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In a another work, the Krasavin team investigated the effect of increasing bulk of substituents in α-position of tetracyclic imidazoline-fused tricyclic seven-membered imines. [58] Hence, they established a reaction process similar to the previous work for the synthesis of the ring expanded product. The examination of the reactions of cyclic imines with Me, Et, Ph and tert-Bu substituents showed that imine with bulky tert-Bu group gave only the ring expanded product.…”
Section: Ring Expansion Reactionsmentioning
confidence: 93%
See 1 more Smart Citation
“…In a another work, the Krasavin team investigated the effect of increasing bulk of substituents in α-position of tetracyclic imidazoline-fused tricyclic seven-membered imines. [58] Hence, they established a reaction process similar to the previous work for the synthesis of the ring expanded product. The examination of the reactions of cyclic imines with Me, Et, Ph and tert-Bu substituents showed that imine with bulky tert-Bu group gave only the ring expanded product.…”
Section: Ring Expansion Reactionsmentioning
confidence: 93%
“…In this method, the ten‐membered ring heterocycles 95 were obtained in low to moderate yields. In a another work, the Krasavin team investigated the effect of increasing bulk of substituents in α‐position of tetracyclic imidazoline‐fused tri‐cyclic seven‐membered imines [58] . Hence, they established a reaction process similar to the previous work for the synthesis of the ring expanded product.…”
Section: Cycloaddition/annulation Reactions On Tri‐cyclic Seven‐membe...mentioning
confidence: 99%